The Competitiveness of Global Port-Cities: The Case of Antofagasta, Chile - Merk, Olaf (OECD Regional Development Working Papers, 2013)
This working paper offers an evaluation of the performance of ports of Antofagasta, an analysis of the impact of the ports on their territory and an assessment of policies in this field. It examines port performance over the last decades and identifies the principal factors that have contributed to it. The effect of the port on economic and environmental questions is studied and quantified where possible. The major policies governing the ports are assessed, along with policies governing transport and economic development, the environment and spatial planning. Based on the report's findings, recommendations are proposed with a view to improving port performance and increasing the positive effects of the ports of Antofagasta